Corporate Market Power in Romania : Assessing Recent Trends, Drivers, and Implications for Competition - Iootty, Mariana; Pop, Georgiana; Pena, Jorge (World Bank, Washington, DC, 2020)
This paper explores firm-level heterogeneity to identify the underlying drivers of market power trends in Romania and the implications for competition and economic growth. The results show that the (sales-weighted) average markup in Romania increased by around 15 percent between 2008 and 2017. A key driving force behind this aggregate trend was the ability of a small fraction of firms -- the top decile firms in the markup distribution -- to increase their markups. These firms do not seem to follow the typical superstar firms' profile: they are smaller, less efficient, and less likely to invest in intangible assets than other firms in the markup distribution and overrepresented in less knowledge-intensive service sectors (for example, the retail and trade sector). This suggests that the increase in markups in Romania might be associated with an environment that is less conducive to competition. A decomposition exercise shows that the increase in aggregate markups has been driven mostly by incumbents rather than new entrants and exiting firms, which could be interpreted as a sign of consolidation of market power among existing firms. The paper also finds that certain firm characteristics matter to explain differences in markup performance: size, age, research and development profile, export propensity, location, and especially ownership. Further, the paper shows that additional productivity dividends are associated with increased competition in Romania. Overall, these findings illustrate potential policy angles that need to be tackled to enhance market contestability and boost productivity growth, such as addressing regulations that restrict entry and rivalry in the retail trade sector, which concentrates a substantial proportion of high-markup firms, as well as promoting competitive neutrality across markets where public and private actors compete.